PENGARUH CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR TEMATIK KELAS IV SEKOLAH DASAR - Wahyu Aji; Kartono Kartono; Suhardi Marli (Universitas Tanjungpura, 2019)
AbstractThe problem in this research was how the influence of contextual teaching and learning (ctl) in Thematic Learning against the results of the grade IV elementary school number 29 Pontianak city. The method used was the experiment with forms of Experimental Design Quaisy design non equivalent control group design. The entire population of students of three classes that add up to 90 people, this research sample was grade IV A of 31 people as a class experiment and grade IV B of 29 people as a class control. Data collection techniques used are measurement techniques and data-collecting instrument was the written test multiple choice-shaped. Based on the analysis of data obtained average results post-test experiments class with an average 76.56 and post-test control class 71.67. Hypothesis test results using t-test (Polled Variance) obtained ???? = 2.566 while for dk (29-31 + 2 = 58) with significant level α = 5% obtained ???? = 1.672, meaning ???? ???????????????????? > ???? , then the Ha received, this proves there was influence contextual teaching and learning (ctl) in thematic learning. Based on the results of the calculation of effect size (ES) obtained ES = 0.47 which included the criteria of medium. Therefore it can be concluded that using Contextual Teaching and Learning (CTL) in Thematic Learning provide positive influence towards learning outcomes grade IV elementary school number 29 Pontianak city. Key words : Contextual Teaching and Learning, Influence, the results of the thematiclearning